IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI ERA DIGITAL - Izzati (Jurnal Ikhtibar Nusantara, 2026)
The digital age has brought about significant changes in society, including in the world of education. Advances in information and communication technology have made it easier to acquire knowledge; however, they have also presented challenges in the form of declining moral standards, increasing individualistic behaviour, the misuse of social media, and the erosion of character values among students. In this context, Islamic Religious Education (IRE) plays a strategic role in shaping students’ character so that they are able to face technological developments wisely and responsibly. This study aims to analyse the implementation of Islamic Religious Education in the character development of students in the digital age. This study employs a library research method using a qualitative descriptive approach. Data were obtained from various books, scientific journals, previous research findings, and documents relevant to character education and IRE. The findings indicate that the implementation of IRE in character development can be achieved through the integration of Islamic values into the learning process, teacher role modelling, the cultivation of religious behaviour, the educational use of digital media, and the strengthening of cooperation between schools, families, and the community. Character values that can be developed through Islamic Religious Education include religiosity, honesty, responsibility, discipline, tolerance, and social concern. With appropriate implementation, Islamic Religious Education can serve as an effective means of shaping a generation of noble character and strong values amidst the increasingly complex tide of digitalisation.